2014
DOI: 10.1021/jf405529b
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Determination of Reference Materials and Natural Isolates by Means of Quantitative 1H NMR Spectroscopy

Abstract: A fast and precise proton nuclear magnetic resonance (qHNMR) method for the quantitative determination of low molecular weight target molecules in reference materials and natural isolates has been validated using ERETIC 2 (Electronic REference To access In vivo Concentrations) based on the PULCON (PULse length based CONcentration determination) methodology and compared to the gravimetric results. Using an Avance III NMR spectrometer (400 MHz) equipped with a broad band observe (BBO) probe, the qHNMR method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
270
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(272 citation statements)
references
References 33 publications
1
270
0
1
Order By: Relevance
“…The synthetic peptides subsequently quantified (Table 5 and Figure S11 to S14) showed that compound 13 contained of 21 % of analysed sample, compound 14 contained 34 % of the peptide while 15 and 16 contained 19 % and 33 % of the total solid of the analysed samples respectively. Given the high purity of compounds 13-16 we suggest that the low percentage of compound per total mass of powder can be attributed to significant retention of water during the freeze-drying process, which is supported by a large water peak (~ 3.3 ppm) in the NMR spectra ( Figure S11-14) similar to the finding of Frank et al 72 analytical data presented shows that the actual quantity compounds were under estimated in the preparation of the stock solution. …”
Section: Peptide Quantification By Nmrsupporting
confidence: 74%
“…The synthetic peptides subsequently quantified (Table 5 and Figure S11 to S14) showed that compound 13 contained of 21 % of analysed sample, compound 14 contained 34 % of the peptide while 15 and 16 contained 19 % and 33 % of the total solid of the analysed samples respectively. Given the high purity of compounds 13-16 we suggest that the low percentage of compound per total mass of powder can be attributed to significant retention of water during the freeze-drying process, which is supported by a large water peak (~ 3.3 ppm) in the NMR spectra ( Figure S11-14) similar to the finding of Frank et al 72 analytical data presented shows that the actual quantity compounds were under estimated in the preparation of the stock solution. …”
Section: Peptide Quantification By Nmrsupporting
confidence: 74%
“…Nuclear magnetic resonance (NMR) spectroscopy is a powerful tool for the purpose of quantitative analysis because of the direct proportionality of signal intensity to the number of resonating nuclei and has found many applications in analytical chemistry [1][2][3][4][5]. Usually quantification is provided using a signal from a chemical reference standard added to the sample (internal referencing).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nowadays, determination of the exact concentration of the isotopically labled internal standards can best be achieved by means of quantitative NMR spectroscopy (q NMR) [31].…”
Section: Analytical Techniques Used To Characterize Stress Induced Mementioning
confidence: 99%